Parental Perspectives on the Emotional, Relational and Logistical Impacts on Siblings of Youth Who Sexually Offend. (9th May 2019) - Gervais, Christine; Romano, Elisa
Abstract : This qualitative study explored parents' perspectives on the collateral consequences of youth sexual offending on siblings through the analysis of interview data among 16 caregivers from 10 Canadian families. Using thematic coding procedures, findings indicated that parents identified a range of safety, emotional and interpersonal impacts on siblings beginning with the criminal justice and child welfare investigations of the sexual offending and extending to siblings' relationships with the offending youth, their caregivers and other relatives. Results demonstrate the need for greater acknowledgement of, and parent‐informed interventions that specifically address the impact of youth sexual offending on siblings by professionals and non‐professionals (e.g. relatives) alike.